Open Service Innovation: The Case of Tourism Firms in Scandinavia - Tor Helge Aas (Journal of Entrepreneurship, Management and Innovation, 2016)

(untitled)
Most empirical research investigating open innovation has focused on the development of new physical products in manufacturing industries, whereas open service innovation has not been researched correspondingly. Services have some characteristics that distinguish them from physical products, which may affect the types of open innovation practice utilised during service innovation processes. Tourism services comprise a subset of services that is particularly distant from tangible products. Therefore, the exploration of how tourism firms utilise different types of open innovation practice offers a valuable opportunity to learn about the nature of open service innovation practices. Thus, this paper addresses the following research question: what types of open innovation practice are utilised during the development of new tourism services? A qualitative case study approach was used to answer the research question. The findings suggest that pecuniary and non-pecuniary inflows of knowledge are utilised during service innovation processes in tourism. However, the stage of the innovation process at which inflows of knowledge are utilised varies systematically with respect to whether the innovation is perceived to be incremental or more radical. The findings also indicate that tourism firms reveal knowledge to other tourism firms in non-pecuniary outbound open innovation processes. However, no example of a pecuniary outbound open innovation practice was identified in this study. Implications for management and further research are discussed in the paper.